A more selective and accurate method than indigo method for measuring dissolved ozone concentration (p-vinylbenzoic acid method). (1st March 2023) - Kawaguchi, Kohei; Hidaka, Taira; Fujiwara, Taku
Highlights: Ozone reacts p -vinylbenzoic acid ( p -VBA) to form p -formylbenzoic acid ( p -FBA). The ozone concentration can be determined from the p -FBA concentration. p -VBA method is more accurate than the indigo method. p -VBA method can be used in the presence of oxidants other than ozone. p -VBA method does not require calibration of the quantitative reagent. Abstract: Dissolved ozone concentration measurement is crucial for ozone treatment. In the most used conventional indigo method, the ozone concentration is measured by the decrease in absorbance due to the loss of the C–C double bond of indigotrisulfonic acid. However, measurement of ozone concentration is difficult when water contains substances that react with C–C double bonds other than ozone. To address this concern, we developed a novel breakthrough method to measure ozone concentration by measuring the p- formylbenzoic acid ( p- FBA) produced after the reaction of p- vinylbenzoic acid and ozone. The formation of p- FBA was almost not caused by other substances (hypochlorous acid, hypobromous acid, permanganate ion and hydrogen peroxide), and its yield to ozone was maintained at 1 in river water, treated wastewater and seawater. In addition, the experimental error is smaller with the new method than with indigo. Furthermore, the new method does not require cumbersome calibration unlike indigo method because highly pure forms of p- FBA are commercially available. p- FBA can be separated by liquid chromatography and detected with highly sensitive ultraviolet and mass spectrometric detectors, and hence easily analyzed simultaneously with other substances. Our new method contributes to extensive ozone treatment and ozonation management. Graphical abstract: Image, graphical abstract